Early postpartum abnormal glucose metabolism subtype differs according to mid-trimester lipid profile in women with gestational diabetes mellitus - Lai, Fenghua; Li, Zeting; Yue, Shufan; Pei, Ling; Xiao, Huangmeng; Li, Zhuyu; Li, Yanbing; Xiao, Haipeng; Cao, Xiaopei (Lipids in health and disease, 2021)
It is unknown whether early postpartum abnormal glucose metabolism (AGM) in women with previous gestational diabetes mellitus (GDM) is related to their mid-trimester lipid profile. The aim of this study was to characterize the mid-trimester lipid profile of women who experienced GDM and developed into different pathophysiologic subtypes of early postpartum AGM. A retrospective cohort study of 498 women with history of GDM was conducted. A 75-g oral glucose tolerance test (OGTT) and plasma lipid measurements were performed at 24-28 weeks of gestation and 6-12 weeks of postpartum. Insulin secretion and sensitivity were estimated using early postpartum OGTT-based indices. Women in the mid-trimester dyslipidemia group had higher postpartum 30-min and 2-h plasma glucose, higher postpartum 2-h plasma insulin, higher postpartum triglyceride (TG), higher postpartum low density lipoprotein cholesterol (LDL-c) concentrations, lower postpartum 30-min insulinogenic index (IGI ), lower postpartum insulin sensitivity index (ISI), and lower postpartum disposition index than those in the normal lipid group (all P < 0.05). Abnormal mid-trimester TG and LDL-c concentrations were associated with postpartum AGM (adjusted odds ratio [OR] = 1.786, 95 % confidence interval [CI] = 1.142-2.425; and adjusted OR = 1.621, 95 % CI = 1.323-2.051, respectively; both P < 0.05). AGM women with low IGI and low ISI had higher mid-trimester total cholesterol and LDL-c concentrations, and AGM women with low ISI had higher mid-trimester TG concentrations than women with NGT or other subtypes of AGM (all P < 0.05). GDM women with abnormal mid-trimester TG and LDL-c were predisposed to early postpartum AGM. Postpartum AGM women who experienced GDM had heterogeneous mid-trimester lipid profile when classified according to their pathophysiologic subtype.